Predator–Prey Coevolutionary Dynamics (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2023)
Coevolutionary arms races between predators and prey generate some of the most dynamic and ecologicallyconsequential evolutionary interactions in nature, producing phenotypic escalation in defensive and offensive traits thatreciprocally drive morphological, physiological, and behavioural divergence on ecological and evolutionary timescales.This study integrated quantitative genetic analysis, population-level genomic data, and long-term field monitoring tocharacterise coevolutionary dynamics in four predator-prey systems in European mountain ecosystems: golden eagle(Aquila chrysaetos) – mountain hare (Lepus timidus), Eurasian lynx (Lynx lynx) – roe deer (Capreolus capreolus), pinemarten (Martes martes) – red squirrel (Sciurus vulgaris), and peregrine falcon (Falco peregrinus) – rock dove (Columbalivia). For each system, we quantified: (i) trait covariation between predator attack efficiency and prey evasion capacity (n= 284 individuals per species; morphometric + kinematic analysis); (ii) genomic signatures of coevolutionary selection atcandidate loci (n = 84 individuals per species; RADseq; 18,484 SNPs); and (iii) 15-year population dynamics showingpredator-prey density oscillations (annual census data 2008–2022). Quantitative genetic analysis confirmed significantheritable variation in evasion traits across all four prey species (mean h2 = 0.42 ± 0.08), and in attack-efficiency traits inpredators (mean h2 = 0.38 ± 0.10). RADseq FST outlier analysis identified candidate coevolutionary loci enriched forlocomotion, sensory perception, and anti-predator behaviour pathways (enrichment 5.8x above genome background; p